Experiences of High School Students about the Predictors of Tobacco Use: a Directed Qualitative Content Analysis - Mahmoud Ghasemi; Leila Sabzmakan (Hamadan University of Medical Sciences, 2015)
Background and Objectives: Tobacco use is one of the most important risk factors that increases the burden of diseases worldwide. Based on the increasing speed of tobacco use, the aim of the present study was to explain the experiences of high school students about the determiners of use and non-use of tobacco (cigarettes and hookah) based on the theory of protection motivation. Materials and Methods: The present study is a qualitative study based on content analysis that has been carried out for five months from 22, November of 2014 to 20, April of 2015 on male high schools in Noshahr. Data were collected in the form of semi-structured interviews from 21 male high school students of whom 7 smoked cigarettes, 7 used hookah and 7 of them did not use any type of tobacco. Data analysis was carried out through the use of directed qualitative content analysis. Results: Data analysis led to the extraction of 99 primary codes that were categorized into 9 predetermined levels of protection motivation theory including perceived sensitivity, perceived intensity, fear, perceived self-efficacy, response expense, efficiency of the perceived answer, external perceived reward, internal perceived reward, protection motivation. The findings of the study showed that the most important predictors for the use of tobacco were the structures of response expense and high perceived rewards and the most important predictors for non-use of tobacco were perceived sensitivity, perceived intensity and high self-efficacy of students. Conclusions: the findings of the present study showed that the pressure from peers, being present in a group using tobacco and the absence of alternative recreational activities are among the most important factors of using tobacco. So, it is suggested that planners of the health department take the comprehensive interventions to improve effective individual and environmental factors of using tobacco so that they could reduce smoking cigarettes and hookah.